Study of Bioactivities of Holarrhena pubescence Growing in Bangladesh (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The stem bark of Holarrhena pubescence was tested for anti-diabetic, analgesic, anti-inflammatory and antidiarrheal activities. After 1, 4 and 12 weeks of treatment protocol in alloxan-induced diabetic rats, it showed very negligible reduction of blood glucose level. In 12 weeks treatment protocol H. pubescence demonstrated that, the extract at 300 and 600 mg/kg bw can reduce blood glucose level by 3 and 4 mmol/l, respectively. Bark extract possessed strong analgesic, anti-diarrheal and mild anti-inflammatory activities. A dose of 600-mg/kg showed 69.50% (p